Chase your shadow: the trials of Oscar Pistorius - Carlin, John (Atlantic Books, 2014)
"The murder trial of Oscar Pistorius will rivet the world's attention in a way no other case has since another famous sportsman, O. J. Simpson, was tried for the murder of his ex wife in 1994. John Carlin brings his own extensive knowledge of South Africa and access to Pistorius himself, as well as to his friends and family, after the death of Reeva Steenkamp to tell the story of the rise and fall of a classically tragic hero. It is the most remarkable sports story ever told - about a man whose legs were amputated at the age of eleven months and ended up running in the Olympic Games - and it is a story too about crime and punishment, love and death that follows Pistorius' trail from South Africa to London, to the United States, to Iceland, to Italy and has at its heart a richly varied and compelling set of characters, among them the beautiful victim, two brilliant rival lawyers and the fascinatingly complex figure of Oscar Pistorius himself."